A Case Report of Pemphigoid Nodularis as Masquerader of Neurotic Excoriations - Chee Hian Tan; Hong Liang Tey (Wolters Kluwer Health, 2020)
Abstract. Introduction:. Pemphigoid nodularis is a rare clinical variant of bullous pemphigoid characterized by both prurigo nodularis-like lesions and pemphigoid-like blisters. Herein, we report a case of pemphigoid nodularis in a cognitively-impaired patient who has been managed as extensive prurigo nodularis with neurotic exocriations for many years. Case presentation:. A 72-year-old Chinese man has been on follow-up at an outpatient Dermatology unit for extensive prurigo nodularis for past 4 to 5 years until an inpatient stay when he was admitted for labile mood and erratic behavior due to the intense pruritus and skin lesions. During the admission, the inpatient team noticed tense hemorrhagic blisters on his right thigh for which histological examination confirmed the diagnosis of bullous pemphigoid. He was treated with oral prednisolone, doxycycline, and nicotinamide, which led to clinical improvement. Discussion:. Pemphigoid nodularis can be easily misdiagnosed as prurigo nodularis. We discuss clinical clues that can raise the suspicion of an underlying immunobullous disorder, including erythematous nodules with a much larger surface area affected by central erosions and ulceration. Pruritus associated with larger areas of erosions and ulceration is clues that lesions can be more than mere excoriations. Conclusion:. It is important for clinicians to be aware of the presentation of prurigo nodularis in association with bullous pemphigoid such that effective treatment can be promptly instituted. This is especially illustrated in this case, as the treatment of bullous pemphigoid not only improved his skin condition but it also improved his psychological health and behavior with the resolution of itch.